2010
DOI: 10.1111/j.1601-183x.2009.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐adducin (Add2) KO mice show synaptic plasticity, motor coordination and behavioral deficits accompanied by changes in the expression and phosphorylation levels of the α‐ and γ‐adducin subunits

Abstract: Adducins are a family of proteins found in cytoskeleton junctional complexes, which bind and regulate actin filaments and actin-spectrin complexes. In brain, adducin is expressed at high levels and is identified as a constituent of synaptic structures, such as dendritic spines and growth cones of neurons. Adducin-induced changes in dendritic spines are involved in activitydependent synaptic plasticity processes associated with learning and memory, but the mechanisms underlying these functions remain to be eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 59 publications
3
38
0
1
Order By: Relevance
“…This brain-specific Add2 mRNA shows dendritic localization. 24,26 In this work we confirmed that TDP-43 interacts with the Add2 PAS DSE in vitro and observed that depletion of TDP-43 in tissue culture cells results in the down-regulation of both the chimeric and endogenous Add2 transcripts. Apparently, this effect was not mediated by the Add2 DSE, as substituting the Add2 DSE with viral E-SV40 and L-SV40 DSEs, which are not TDP-43 targets, still resulted in a decrease of Add2 mRNA levels in vivo after TDP-43 depletion.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…This brain-specific Add2 mRNA shows dendritic localization. 24,26 In this work we confirmed that TDP-43 interacts with the Add2 PAS DSE in vitro and observed that depletion of TDP-43 in tissue culture cells results in the down-regulation of both the chimeric and endogenous Add2 transcripts. Apparently, this effect was not mediated by the Add2 DSE, as substituting the Add2 DSE with viral E-SV40 and L-SV40 DSEs, which are not TDP-43 targets, still resulted in a decrease of Add2 mRNA levels in vivo after TDP-43 depletion.…”
Section: Introductionsupporting
confidence: 70%
“…In fact, Add2 has a key role in the assembly of synapses, control of synaptic plasticity and stability, associated to LTP, LTD, motor abilities and learning. [22][23][24][25] The evidenced involvement of TDP-43 in Add2 mRNA stability can be considered relevant also at the light of its possible impact on the neurodegenerative processes associated to ALS and FTLD. The exact molecular mechanisms associated to ALS and FTLD are not completely understood, since TDP-43 cytoplasmic inclusions might have a toxic gain of function or loss of function by sequestering nuclear TDP-43 (or both), disrupting its role in RNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…␤-Adducin is a cytoskeleton-associated protein that is predominantly expressed in the brain, where it is a constituent of synapses, dendritic spines, and growth cones (35)(36)(37). It has been shown to regulate neuronal cytoarchitecture, long-term potentiation, motor coordination, and learning (37)(38)(39). Therefore, we were interested to see whether ␤-adducin is a novel brain substrate of GSK3.…”
Section: Identification Of Novel Gsk3mentioning
confidence: 99%